Repeated ethanol exposure and withdrawal alters angiotensin‐converting enzyme 2 expression in discrete brain regions: Implications for SARS‐CoV‐2 neuroinvasion. (1st January 2023) - Balasubramanian, Nagalakshmi; James, Thomas D.; Selvakumar, Govindhasamy Pushpavathi; Reinhardt, Jessica; Marcinkiewcz, Catherine A.
Abstract: Background: People with alcohol use disorder (AUD) may be at higher risk for COVID‐19. Angiotensin‐converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) are required for cellular entry by SARS‐CoV‐2, but information on their expression in specific brain regions after alcohol exposure is limited. We sought to clarify how chronic alcohol exposure affects ACE2 expression in monoaminergic brainstem circuits and other putative SARS‐CoV‐2 entry points. Methods: Brains were examined for ACE2 using immunofluorescence after 4 weeks of chronic intermittent ethanol (CIE) vapor inhalation. We also examined TMPRSS2, Cathepsin L, and ADAM17 by Western blot and RAS pathway mediators and pro‐inflammatory markers via RT‐qPCR. Results: ACE2 was increased in most brain regions following CIE including the olfactory bulb (OB), hypothalamus (HT), raphe magnus (RMG), raphe obscurus (ROB), locus coeruleus (LC), and periaqueductal gray (PAG). We also observed increased colocalization of ACE2 with monoaminergic neurons in brainstem nuclei. Moreover, soluble ACE2 (sACE2) was elevated in OB, HT, and LC. The increase in sACE2 in OB and HT was accompanied by upregulation of ADAM17, an ACE2 sheddase, while TMPRSS2 increased in HT and LC. Cathepsin L, an endosomal receptor involved in viral entry, was also increased in OB. Alcohol can increase Angiotensin II, which triggers a pro‐inflammatory response that may upregulate ACE2 via activation of RAS pathway receptors AT1R/AT2R. ACE2 then metabolizes Angiotensin II to Angiotensin (1‐7) and provokes an anti‐inflammatory response via MAS1. Accordingly, we report that AT1R/AT2R mRNA decreased in OB and increased in the LC, while MAS1 mRNA increased in both OB and LC. Other mRNAs for pro‐inflammatory markers were also dysregulated in OB, HT, raphe, and LC. Conclusions: Our results suggest that alcohol triggers a compensatory upregulation of ACE2 in the brain due to disturbed RAS and may increase the risk or severity of SARS‐CoV‐2 infection. Abstract : Angiotensin converting enzyme‐2 (ACE2) levels were elevated across multiple brain regions implicated in SARS‐CoV‐2 entry into the CNS after alcohol exposure in mice, including the olfactory bulb, hypothalamus, and brainstem. Soluble ACE2 levels increased alongside changes in TMPRSS2 and ADAM17, which cleaves cellular ACE2 to facilitate viral entry and fusion. Alcohol upregulates ACE2 expression as a compensatory response to inflammatory RAS signaling, and as a result may increase the risk of SARS‐CoV‐2 neuroinvasion and post‐acute neurological sequelae.